Emotional Regulation in the Hadith on the Prohibition of Anger: A Psychological Analysis and Implications for Modern Anger Management Therapy - Khamil Yahya; Mohd Remli Johan; Maya Febriana (Yayasan Albahriah Jamiah Indonesia, 2025)
The urgency of emotion management in contemporary society is increasingly prominent, as evidenced by the rising incidence of interpersonal violence and the growing prevalence of emotion regulation disorders reported in global epidemiological surveys. Therefore, an integrated ethical and psychological foundation is needed to formulate adaptive anger management strategies. This study aims to analyze the normative meaning structure of the hadith prohibiting anger through critical textual analysis and to integrate these findings with contemporary emotion regulation theory to formulate a therapeutic framework for further testing. Using a qualitative-analytical approach, this study examines hadith texts on anger from major hadith collections through inductive thematic analysis and cross-validation, then connects them to models of emotion regulation such as cognitive control, reappraisal, response inhibition, and adaptive coping strategies. The study shows that the hadith prohibiting anger contains three core dimensions: strengthening impulse control, internalizing self-awareness, and activating volition as the basis for adaptive behavior. These dimensions are consistent with psychological mechanisms such as cognitive monitoring of emotional triggers, restructuring the interpretation of frustrating situations, inhibiting aggressive responses, and selecting more prosocial behavioral alternatives. The integration of the two results in a values-based therapeutic framework that emphasizes reflective awareness, moral principle-based self-control, and cognitive-behavioral modification techniques as the foundation for anger management interventions. This research contributes to strengthening the theoretical foundation for the relationship between hadith ethics and emotion regulation by offering a model with potential therapeutic application. However, further empirical testing is still needed.